2016
DOI: 10.1007/s00405-016-4166-3
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal mesenchymal stem cell administration ameliorates allergic rhinitis in the murine model

Abstract: Previous studies showed that bone marrow-derived mesenchymal stem cells (BMSCs) could ameliorate a variety of immune-mediated and inflammatory diseases due to their immunomodulatory and anti-inflammatory effects. In this study, we developed a mouse model of ovalbumin (OVA) induced allergic inflammation in the upper airways and evaluated the effects of the intraperitoneal administration of BMSCs on allergic inflammation. Twenty-five BALB/c mice were divided into five groups; group I (control group), group II (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…It has been shown that intraperitoneal administration of bone marrow MSCs is the potential to modulate the allergic asthma reaction. Soon after injection into the peritoneal cavity, these cells easily migrate to the pulmonary niche and exert immunomodulatory capacity [ 73 , 74 ].
Fig.
…”
Section: Mechanisms Involved In the Therapeutic Effects Of Mscs In Exmentioning
confidence: 99%
“…It has been shown that intraperitoneal administration of bone marrow MSCs is the potential to modulate the allergic asthma reaction. Soon after injection into the peritoneal cavity, these cells easily migrate to the pulmonary niche and exert immunomodulatory capacity [ 73 , 74 ].
Fig.
…”
Section: Mechanisms Involved In the Therapeutic Effects Of Mscs In Exmentioning
confidence: 99%
“…MSCs are capable of differentiating into a number of cell types and are of high translation potential for clinical applications. MSCs are found to migrate to the airway under inflammation and exert reparative function 11‐13 . A number of previous studies have demonstrated the great potential of MSCs in treating AR 9,11,14‐16 .…”
Section: Introductionmentioning
confidence: 99%
“…A similar discovery was made in a separate study. It was found that bone marrow-derived MSCs migrated to the nasal and lung tissues following intraperitoneal delivery and ameliorated to the airway remodeling and airway inflammation both in the upper and lower airways via the inhibition of Th2 immune response in the mouse model of AR [40]. [41].…”
Section: 2mentioning
confidence: 99%